2020
DOI: 10.1103/physrevresearch.2.033342
|View full text |Cite
|
Sign up to set email alerts
|

Signature of band inversion in the antiferromagnetic phase of axion insulator candidate EuIn2As2

Abstract: We have performed angle-resolved photoemission spectroscopy on EuIn 2 As 2 which is predicted to be an axion insulator in the antiferromagnetic state. By utilizing soft-x-ray and vacuum-ultraviolet photons, we revealed a three-dimensional hole pocket centered at the point of the bulk Brillouin zone together with a heavily hole-doped surface state in the paramagnetic phase. Upon entering the antiferromagnetic phase, the band structure exhibits a marked reconstruction characterized by the emergence of an "M"-sha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 39 publications
(57 reference statements)
3
14
0
Order By: Relevance
“…S7 ). These results indicate that 1) the observed spin polarization has a nonmagnetic origin, 2) TRS is preserved as expected for a topological surface state ( 2 , 23 , 37 , 38 ), and 3) the topological character is strong and not influenced by in-plane layered ferromagnetism, as opposed to what has been observed in MnBi 2 Te 4 for the out-of-plane direction of the magnetization ( 14 ). As outlined above, calculations predict the presence of two split P bands, which should carry opposite spins.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…S7 ). These results indicate that 1) the observed spin polarization has a nonmagnetic origin, 2) TRS is preserved as expected for a topological surface state ( 2 , 23 , 37 , 38 ), and 3) the topological character is strong and not influenced by in-plane layered ferromagnetism, as opposed to what has been observed in MnBi 2 Te 4 for the out-of-plane direction of the magnetization ( 14 ). As outlined above, calculations predict the presence of two split P bands, which should carry opposite spins.…”
Section: Resultssupporting
confidence: 54%
“…Following theoretical predictions, the localized nature of 4f electrons may guarantee not only a clear distinction between electronic states but also a reduced hybridization of the magnetic and topological states, possibly resulting in a distinct control of magnetic and topological properties ( 8 ). To date, a few f- based magnetically ordered AFI candidates have been realized, namely EuIn 2 As 2 , EuSn 2 As 2 and EuSn 2 P 2 ( 19 23 ). EuIn 2 As 2 and EuSn 2 As 2 both have a = 2 invariant, i.e., a nontrivial topology ( 8 , 19 ), yet a complete spectroscopic characterization with spin analysis for materials in this family is lacking.…”
mentioning
confidence: 99%
“…The top of the pz band of EuIn2As2 is positioned ~0.1 eV above the Fermi energy; therefore, the bandgap originates from mixing between the conduction and valence bands due to spin-orbit coupling. It is shown that EuIn2As2 can exhibit a nontrivial topological electronic state, as discussed in the reports by Xu et al 26 and Sato et al 27 When As is substituted by P, the top of the pz band sinks below the Fermi level. EuIn2P2 is therefore a semiconductor with a bandgap of ~0.4 eV.…”
Section: First-principles Calculationsmentioning
confidence: 78%
“…23,24 EuIn2As2 and SrSn2As2 have also attracted considerable attention as topological materials. [26][27][28][29] Interestingly, topologically nontrivial electronic states and efficient thermoelectric properties are often observed in similar materials, such as (Bi,Sb)2(Te,Se)3 and (Pb,Sn)(Te,Se), because these compounds have the same required material features, including a narrow bandgap, heavy constituent elements, and large spin-orbit coupling. [30][31][32][33][34][35][36][37] Therefore, it is worth investigating the thermoelectric properties of EuIn2As(P)2 and SrSn2As2.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 EuIn2As2 and SrSn2As2 have also attracted considerable attention as topological materials. [26][27][28][29] Interestingly, topologically nontrivial electronic states and efficient thermoelectric properties are often observed in similar materials, such as (Bi,Sb)2(Te,Se)3 and (Pb,Sn)(Te,Se), because these compounds have the same required material features, including a narrow bandgap, heavy constituent elements, and large spin-orbit coupling. [30][31][32][33][34][35][36][37] Therefore, it is worth investigating the thermoelectric properties of EuIn2As(P)2 and SrSn2As2.…”
Section: Introductionmentioning
confidence: 99%